Optimasi usahatani ternak kambing peranakan ettawa di Sumberpucung Malang Jawa Timur=Optimization of Goat Raising in the Mixed Farming at Sumberpucung, Malang, East Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
A survey was conducted to determine the optimum farming activities in order to find the maximum income and to determine the percent income coming from goat raising. The existing farm income was found to be Rp.353,965. Â±Rp. 186,609. and 29,83 % ( Rp. 106,873. Â± Rp. 60,461.) of which was coming from goat raising. The optimum combination of farming activities was the combination of homestead coffee production and goat raising. The maximum income was found to be Rp. 1,162,743. per year, of which 33.37 % (Rp. 387,960. per year) was coming from goat raising of seven heads or 1.2 animal unit. Net present value and benefit/cost ratio of this goat raising were Rp. 110,676. and 1.148, respectively.